Identification of Osteochilus spilurus (Cyprinidae: Labeoninae) from North Lampung using meristic and cytochrome b gene - Kurniawan, Ardiansyah; Pramono, Dasa Yuli; Indrayati, Artin; Triswiyana, Ira (Universitas Malikussaleh, 2022)
Osteochilus spilurus is one of native fish in Indonesia. This species from North Lampung has variations in body shape with populations in Bangka and Belitung. Morphological plasticity and genetic variation are potential causes of these differences. To confirm this, it is necessary to identify molecular using the mitochondrial cytochrome b (cyt b) gene. Fish samples from North Lampung had morphological characters matched to the description of O. spilurus. This research specimen was registered at the Bogor Zoological Museum as a supplementary note from Lampung. The phylogenetic construction shows a closer relationship between fish samples from North Lampung and O. spilurus from Bangka-Belitung, but there is a wide genetic distance between them. Genetic variation between islands that occur is predicted due to differences in ancient river flows in the past and the geographical isolation of the oceans for thousands of years.Keywords: Cytochrome b; Lampung; Osteochilus spilurus; Genetic Variation